2010
DOI: 10.4995/wrs.2004.566
|View full text |Cite
|
Sign up to set email alerts
|

Critical points in the transport of commercial rabbits to slaughter in Spain that could compromise animals' welfare.

Abstract: ABSTRACT:The welfare of commercial rabbits depends on the attitudes and handling procedures used by farmers, hauliers and abattoir personnel, as well as the transport logistics. Many studies have been performed on commercial rabbit production but less attention has been paid to identifying critical points during the whole transport procedure. In this study, a survey of rabbit transport was performed in Spanish abattoirs to determine the parts of the process that most compromise the animal's welfare. Data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(57 citation statements)
references
References 6 publications
0
55
0
Order By: Relevance
“…In Spain, journey times for commercial rabbits (to the abattoir) are relatively short, typically less than 3 h (Buil et al, 2004), but, as has been shown previously in other species, poor handling during even relatively short journeys can jeopardize welfare and decrease economic benefits (Agnes et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Spain, journey times for commercial rabbits (to the abattoir) are relatively short, typically less than 3 h (Buil et al, 2004), but, as has been shown previously in other species, poor handling during even relatively short journeys can jeopardize welfare and decrease economic benefits (Agnes et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Meat quality not only includes nutritional properties such as meat texture, colour and sensory characteristics, but also perceptions about the conditions of animal production in relation to animal welfare and healthiness (Dalle Zotte, 2002;Trocino and Xiccato, 2006). In the food production chain, which involves all of the processes between the farm and the fork, transport to slaughter can have a negative impact on the animals and on the fi nal product (Buil et al, 2004). In recent years, the number of abattoirs in many European countries has decreased, thereby increasing the average distance between the farm and the abattoir (Knowles, 1999) and underlining the importance of improving transport conditions for domestic animals in general.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, this area is placed outside, and very few abattoirs provide an enclosed area equipped with forced ventilation and water-misting sprays as a control strategy for adverse environmental conditions (Verga et al, 2009). In a survey of Spanish rabbit abattoirs (Buil et al, 2004), it was found that, before slaughter, there is a short lairage time where animals are kept in the same multi-floor transport cages in a holding area near the stunning facilities. About 80% of the abattoirs surveyed used multi-floor cages during this period with an average capacity at the holding area for 250 (range 45 to 1,500).…”
Section: Water and Feeding Interval Journey Times And Resting Periodsmentioning
confidence: 99%
“…They concluded that, in order to have an effect on meat quality, the threshold for stress was probably higher than the threshold needed to have an effect on welfare indicators. Buil et al (2004), in a survey of Spanish rabbit abattoirs, found that handling procedures differed widely among farms, especially regarding cage size (ranging from 1,430 cm² to 10,000 cm²). Loading facilities were adequate but only a few haulers had received specific training courses.…”
Section: Means Of Transportmentioning
confidence: 99%
See 1 more Smart Citation